Pemanfaatan Jeruk Purut (Citrus Hystrix) Sebagai Biolarvasida - Titik lestari (Poltekkes Kemenkes Surakarta, 2016)
Absctract: Citrus hystrix, Biolarvicides. Insectisides and pestisides were used as larvicides to control mosquito vector Aedes aegypti particularly. Some research suggested there had been a larvae resistance to pesticides. Biolarvicides with basic ingredients plant was another alternative that can be used. Lime (Citrus hystrix) was one of plants that often used as biolarvicides, both lits fruit and leaves. This paper aimed to know about chemical compound in lime and its potential as biolarvicidal. Research methods was literature review from several research journals. The results showed that the presence of coumpounds were essential oil, flavonoids, saponins, terpeesn, limonoids, citronellal, linalool, citronellol, acetate citronelil, kariofilin and geraniol. LC50 of lime leaves as biolarvicides againts the third instar larvae of Aedes aegypti was 279.882 ppm, biolarvicides oxicity values (LC90) was 4000 ppm with the lethal time (LT90) was 12.67 hours. Based on results of this study concluded that the presence of the chemical content of Citrus hystrix plant potential as biolarvicides.